Visualization Components for Persistent Conversations - Fiore, Andrew; Smith, Marc A. (2000)
An appropriately designed interface to persistent, threaded conversations could reinforce socially beneficial behavior by prominently featuring how frequently and to what degree each user exhibits such behaviors. Based on the data generated by the Netscan data-mining project [9], we have developed a set of tools for illustrating the structure of discussion threads like those found in Usenet newsgroups and the patterns of participation within the discussions. We describe the benefits and challenges of integrating these tools into a multi-faceted dashboard for navigating and reading discussions in social cyberspaces like Usenet and related interaction media. Visualizations of the structure of online discussions have applications for research into the sociology of online groups as well as possible interface designs for their members.